Perbandingan Morfometrik dan Meristik Lamun Halophila ovalis di Perairan Pulau Serangan dan Tanjung Benoa, Bali - Putri, I Gusti Ayu Ricca Mahatma; Dirgayusa, I Gusti Ngurah Putra; Faiqoh, Elok (Journal of Marine and Aquatic Sciences, 2017)
Halophila ovalis is a type of seagrass that has a round oval shape that can live in waters that have a muddy sand substrate. Morphometric and meristic are used to describe the waters where seagrass life seen from the morphology of leaves, rhizomes and roots. Morphometrics is a measure to determine the quantitative morphology of an organism structure and Meristik is a calculation to know the sum of a part of an organism.This research was conducted in December 2016-February 2017 with purposive sampling method at 10 observation station in Serangan Island and Tanjung Benoa. Data analyzed with descriptive analysis, Sturges criteria and Similarity Index of Morisita. Based on the results of leaf length study ranged from 9.4-51.3 mm, leaf width ranged from 6.7-19.8 mm, the number of leaf bones ranged from 10- 21 pairs, the length of the petiole ranges from 4.5 to 55.6 mm, the diameter of the petiole ranged from 0.03 - 1.4 mm, the length of rhizoma ranged from 6.2- 41.2 mm, diameter of rhizoma ranged from 0.04 -1.8 mm and root length ranged from 7.5-89 mm. By categorizing morfometrik-meristic seagrass H. ovalis , hence formed value of each research station gaze which will describe similarity between stations. In the similarity index of morisita, the research station in Serangan and Tanjung Benoa waters has similarity of morphometry - meristic very similar to 92.8% equality.